Addressing Internet training issues for people with Parkinson's disease. - Stewart F; Worrall L; Egan J; Oxenham D (Advances in Speech Language Pathology, 2004)
The Internet enables access to information, services, support and participation in leisure opportunities. Some populations, including people with disabilities, lack access to these opportunities through the Internet. Barriers may include finances, physical access, lack of resources and inaccessible websites. Limited access to Internet training is an additional barrier for people with communication impairments. People with Parkinson's disease (PD) may have difficulty accessing usual Internet training due to high-level language, cognitive and physical limitations. Aphasia-friendly Internet training materials were trialed with this population to investigate if participants could learn to use the Internet and would benefit from Internet training. The tutors' experience was also investigated using qualitative measures. Seven people with PD were matched with volunteer tutors. These pairs met for six Internet training lessons using training materials available as a free download from: http://dexter.shrs.uq.edu.au/cdaru/aphasiagroups/. Pre and post-test Internet skills assessments and attitudinal questionnaires were conducted. Significant differences between pre and post-test scores were found. Participants reached varying levels of independence on Internet tasks. Favorable outcomes were reported by participants, and tutors reported a positive experience. Further investigation is recommended to determine the efficacy of this approach compared with other training avenues and with other communication-impaired populations. Practical and theoretical implications for speech pathology practice are discussed.